An enumerative algorithm for the maximum clique problem - Mustafa, Mamat; Suyudi, M.; Sukono, .; Bon, A.T. (2019)
Partial enumerative algorithms are presented for maximum clique problems which are very easy to implement. Search results for efficient implementation of any graph for randomly generated graphs of up to 10 vertices and more than ten sides. Appropriate specifications are also provided for testing problems to facilitate future comparisons. In addition, to understand the maximum clique search without using any software. Search results are presented in the form of examples.